Bioremediation of copper polluted wastewater-like nutrient media and simultaneous synthesis of stable copper nanoparticles by a viable green alga. (August 2021) - Žvab, Urška; Kukulin, Danijel Stojković; Fanetti, Mattia; Valant, Matjaz
Graphical abstract: Highlights: Chlamydomonas reinhardtii can remove cupric ion from wastewater-like media. During bioremediation, valuable sub-10 nm copper nanoparticles are biosynthesized. Viable alga is crucial for efficient bioremediation and biosynthesis. Algal hydrogen photoproduction do not improve bioremediation and biosynthesis. Affinity of copper nanoparticles for organic objects promises their recovery. Abstract: Environmentally benign, algae-mediated biosynthesis of valuable copper-based materials in wastewater, combined with cupric ion (Cu 2+ ) bioremediation, has the potential to reduce the cost of wastewater treatment and generate high quality biosolids. This study investigated the ability of a wild-type strain of Chlamydomonas reinhardtii to bioremediate free Cu 2+ in wastewater-like nutrient media during the biosynthesis of copper nanoparticles (Cu NPs). The color of supernatants from treated Cu-polluted media provided a first indication of Cu-based NPs formation in the aqueous phase. Analysis by fluorescein diacetate hydrolysis, observations of cell morphology, and algal regrowth experiments after treatment showed that algal viability was crucial for efficient Cu 2+ reduction to Cu NPs. UV–vis absorption spectroscopy demonstrated that sulfur-free medium, which enables sustained hydrogen photoproduction in alga, was not the most efficient in NPs formation. Dark-field scanning transmission electron microscopy (STEM) images overlapped with Cu signal map from energy dispersive X-ray spectrometry (EDS) and high-resolution transmission electron microscopy confirmed the presence of polydisperse, spherical, and well-dispersed sub-10 nm Cu NPs crystallites exclusively in algae-treated heavily Cu-polluted media (10 mg L −1 ). STEM and EDS also demonstrated the affinity of Cu NPs for carbon-rich (organic) objects. Overall, this study demonstrates the feasibility of Cu 2+ bioremediation from the wastewater-like complex nutrient media and the simultaneous biosynthesis of Cu NPs by viable green microalga.